Evaluation of a semi-supervised self-adjustment fine-tuning procedure for hearing aids. (1st February 2023) - Gößwein, Jonathan Albert; Rennies, Jan; Huber, Rainer; Bruns, Tobias; Hildebrandt, Andrea; Kollmeier, Birger
Abstract: Objective: This study investigated the effects of different adjustment criteria and sound scenes on self-adjusted hearing-aid gain settings. Self-adjusted settings were evaluated for speech recognition in noise, perceived listening effort, and preference. Design: This study evaluated a semi-supervised self-adjustment fine-tuning procedure that presents realistic everyday sound scenes in a laboratory environment, using a two-dimensional user interface, and enabling simultaneous changes in amplitude and spectral slope. While exploring the two-dimensional space of parameter settings, the hearing-aid users were instructed to optimise either listening comfort or speech understanding. Study sample: Twenty experienced hearing aid users (median age 69.5 years) were invited to participate in this study. Results: Adjustment criterion and sound scenes had a significant effect on preferred gain settings. No differences in signal-to-noise ratios required for 50% speech intelligibility or in the perceived listening effort were observed between the adjusted settings of the two adjustment criteria. There was a preference for the self-adjusted settings over the prescriptive first fit. Conclusions: Listeners could reliably select their preferred gains to the two adjustment criteria and for different speech stimuli.